Pengembangan Video Pembelajaran Berbantuan Canva Pada Pelajaran IPAS Kelas IV Di Sekolah Dasar - Maisarah; Nuke Safria Yusnita (Program Studi PGSD Universitas Madako Tolitoli, 2024)
Multimedia is very useful in supporting student learning activation, so in today's era there are many learning platform offerings in the form of applications that can be used such as Canva. Product development the Canva multimedia to produce learning videos that can make it easier for teachers to convey concepts in science lessons, especially on the unique material of the habits of the community around me and make it easier for students to understand a material, there is the purpose of this research to be carried out. Development research was chosen as this type of research in analyzing the feasibility of using Canva-assisted learning video products developed, with reference to the design of Thiagarajan and Semmel development models known as 4-D models. The study involved linguists, learning material experts, and learning media experts. The results of the study, namely the validity test of material experts, media experts and linguists, obtained an average percentage of final score of 91.24% with very valid criteria. It can be concluded that the development of learning videos is suitable for use in the learning process, so that the results of its development can contribute to helping teachers in presenting learning that stimulates student learning interest.